Visual but not motor processes predict simple visuomotor reaction time of badminton players - Hülsdünker, T.; Strüder, H. K.; Mierau, A. (European Journal of Sport Science, 2018)
The athlete`s brain exhibits significant functional adaptations that facilitate visuomotor reaction performance. However, it is currently unclear if the same neurophysiological processes that differentiate athletes from non-athletes also determine performance within a homogeneous group of athletes. This information can provide valuable help for athletes and coaches aiming to optimize existing training regimes. Therefore, this study aimed to identify the neurophysiological correlates of visuomotor reaction performance in a group of skilled athletes. In 36 skilled badminton athletes, electroencephalography (EEG) was used to investigate pattern reversal and motion onset visual-evoked potentials (VEPs) as well as visuomotor reaction time (VMRT) during a simple reaction task. Stimulus-locked and response-locked event-related potentials (ERPs) in visual and motor regions as well as the onset of muscle activation (EMG onset) were determined. Correlation and multiple regression analyses identified the neurophysiological parameters predicting EMG onset and VMRT. For pattern reversal stimuli, the P100 latency and age best predicted EMG onset (r = 0.43; p = .003) and VMRT (r = 0.62; p = .001). In the motion onset experiment, EMG onset (r = 0.80; p < .001) and VMRT (r = 0.78; p < .001) were predicted by N2 latency and age. In both conditions, cortical potentials in motor regions were not correlated with EMG onset or VMRT. It is concluded that previously identified neurophysiological parameters differentiating athletes from non-athletes do not necessarily determine performance within a homogeneous group of athletes. Specifically, the speed of visual perception/processing predicts EMG onset and VMRT in skilled badminton players while motor-related processes, although differentiating athletes from non-athletes, are not associated simple with visuomotor reaction performance.